1991
DOI: 10.1007/bf00925817
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of children's social problem-solving skills in hypothetical and actual conflict situations

Abstract: This study compared the social problem-solving skills of 57 maladjusted and 57 well adjusted first and second graders in a series of hypothetical and actual provocations. All children were asked how they would react to four video-taped provocations involving same-age peers. They were also exposed to three provocations simulated by a peer-confederate; their verbal and nonverbal behaviors were videotaped. Multivariate analyses of variance indicated that, overall, maladjusted subjects displayed less assertiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
0
16
1
1
Order By: Relevance
“…There are some limitations regarding the current findings, which will have implications for future work. First, data in studies 1 and 2 were gathered by children's responses to hypothetical scenarios, which rely on children's explicit recognition and reporting of often-unconscious processes (Orobio de Castro et al, 2002;Vitaro & Pelletier, 1991). Studies 1 and 2 also use self-reports of loneliness, depressive symptoms, and cognitions, which could have resulted in the problem of shared method variance.…”
Section: Implications For Interventionsmentioning
confidence: 99%
“…There are some limitations regarding the current findings, which will have implications for future work. First, data in studies 1 and 2 were gathered by children's responses to hypothetical scenarios, which rely on children's explicit recognition and reporting of often-unconscious processes (Orobio de Castro et al, 2002;Vitaro & Pelletier, 1991). Studies 1 and 2 also use self-reports of loneliness, depressive symptoms, and cognitions, which could have resulted in the problem of shared method variance.…”
Section: Implications For Interventionsmentioning
confidence: 99%
“…In contrast, in the study by Mize & Cox (1990), a relationship was found between hypothetical responses and both behavioural observations and evaluations by others. It may be that role‐playing is too artificial and unrealistic to be used as a measure of real‐life behaviour, as both Mize & Cox (1990) and Vitaro & Pelletier (1991) have suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies have – to our knowledge – assessed both hypothetical responses and actual behaviour in comparable conflict situations (Dodge 1986; Vitaro et al. 1989; Vitaro & Pelletier 1991). Real‐life situations were found to better differentiate between children with and without behaviour problems than hypothetical situations.…”
Section: Introductionmentioning
confidence: 99%
“…In de realistische Dominosituatie lieten de LVB-kinderen met externaliserende gedragsproblemen meer agressief gedrag zien dan de LVB-kinderen zonder deze problemen. In tegenstelling tot onderzoek bij normaal begaafde kinderen waarin steeds slechts e´e´n van beide methoden onderscheid maakte tussen kinderen met en zonder gedragsproblemen (Mize & Cox, 1990;Mize & Ladd, 1988;Vitaro & Pelletier, 1991), liet dit onderzoek zien dat zowel de hypothetische als de realistische testsituatie onderscheid kan maken tussen de twee groepen.…”
Section: Resultatenunclassified